Solitary Fibrous Tumor of the Orbit: A Case Report And Review of the Literature - (:unkn) unknown (TURKISH NEUROSURGICAL SOC, 2015)
Solitary fibrous tumor (SFT) is a rare, benign, spindle cell tumor that is most commonly found in the visceral pleura. The orbit is one of the most common extrapleural sites of occurrence. Though they can be seen in any age, they typically present in adults with proptosis as the prominent symptom. They show no significant gender predominance. Orbital solitary fibrous tumors routinely exhibit a benign course, but malignant forms with an increased propensity for local recurrence have been reported. Histopathologically, they share similar features with hemangiopericytoma, which is much more common. The diagnosis of SFT depends on the diffuse and intense positivity of CD34 staining by immunohistochemistry (14). Here, we report a case of SFT, which presented with proptosis and double vision on lateral gaze. We describe the clinical, radiographic, histopathological, and immunohistochemical findings. We also provide a discussion on its origin and differential diagnosis in the light of relevant literature.
Keywords: Solitary fibrous tumor; Orbit; CD34; CT